2011
DOI: 10.2139/ssrn.1932091
|View full text |Cite
|
Sign up to set email alerts
|

The Causal Effect of Education on Health: What is the Role of Health Behaviors?

Abstract: In this paper we investigate the contribution of health related behaviors to the education gradient, using an empirical approach that addresses the endogeneity of both education and behaviors in the health production function. We apply this approach to a multi-country data set, which includes 12 European countries and has information on education, health and health behaviors for a sample of individuals aged 50+. Focusing on self reported poor health as our health outcome, we find that education has a protectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 42 publications
6
97
0
4
Order By: Relevance
“…In addition, the difference in health status between more and less educated individuals may increase over the years, for example because more educated individuals adopt more healthy behaviours whose effects manifest in the long term. Brunello et al () found a substantial long‐term effect of education‐induced health behaviours on individual health outcomes for European countries. Ross and Wu () and Prus () show, with US and Canadian data respectively, that the difference in health status between more and less educated individuals is larger for older individuals.…”
Section: Age As a Moderator Of The Relationship Between Education Andmentioning
confidence: 99%
“…In addition, the difference in health status between more and less educated individuals may increase over the years, for example because more educated individuals adopt more healthy behaviours whose effects manifest in the long term. Brunello et al () found a substantial long‐term effect of education‐induced health behaviours on individual health outcomes for European countries. Ross and Wu () and Prus () show, with US and Canadian data respectively, that the difference in health status between more and less educated individuals is larger for older individuals.…”
Section: Age As a Moderator Of The Relationship Between Education Andmentioning
confidence: 99%
“…Furthermore, both health and wellbeing also vary with education (Ross & Wu, ; Cutler & Lleras‐Muney, , ; Brunello, Fort, Schneeweis, & Winter‐Ebmer, ). Meeks and Murrell (), for instance, studied 1177 participants at a mean age of 67.4 years, and then three more times at 6‐month intervals.…”
Section: Personality As a Predictor Of Health And Wellbeingmentioning
confidence: 99%
“…Highly educated individuals make healthier lifestyle choices; they are healthier and live longer. The literature has documented significant associations between education, general health, 1‐6 and health behaviors 5,7‐14 …”
Section: Introductionmentioning
confidence: 99%